Екологічні особливості водних грибів Національного природного парку «Гетьманський» - Кузнєцов, М.О. (Львів : Інститут екології Карпат НАН України, 2021)
First data about biodiversity and some ecological features (abundance, season dynamics) of the aquatic fungi biota in the different natural reservoirs of the Hetmanskyi National Nature Park are given
Kuznietsov M. Ecological features of aquatic fungi of the National Nature Park “Hetmanskyi”
Keywords: водні гриби; біорізноманіття; екологія; Україна